Nahdlatul Ulama Dalam Merawat Moderasi Beragama Di Kabupaten Fakfak Papua Barat - Rumoning, Sari Indrawati; Iribaram, Suparto; Rusdi Rasyid, Muhammad; Sunatar, Bambang; Abdillah, Fardan (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the contributions and strategies of Nahdlatul Ulama (NU) in strengthening religious moderation in Fakfak Regency, West Papua. The study employed a qualitative descriptive method with Islamic education and phenomenological approaches. Primary and secondary data were collected through observation, interviews, and documentation. Data were analyzed through the processes of data reduction, data presentation, and conclusion drawing. The findings reveal that Nahdlatul Ulama plays a significant role in promoting and maintaining religious moderation through various programs and activities aimed at strengthening the values of tolerance, harmony, and social cohesion. Its contributions are manifested through interfaith dialogue, the reinforcement of Aswaja An-Nahdliyah values, collaboration with local governments and the Religious Harmony Forum (FKUB), and the development of moderate-minded youth cadres. The strategies implemented include cultural approaches based on local wisdom, inclusive and friendly da’wah, and the utilization of social media and local media as educational platforms. The impact of these efforts can be seen in the establishment of harmonious interreligious relations, increased awareness among younger generations regarding the importance of tolerance, and stronger cooperation among religious institutions. This study highlights the importance of strengthening the local wisdom philosophy of “One Stove, Three Stones,” optimizing youth participation, and developing flexible and contextual communication strategies to reinforce religious moderation within multicultural communities.